The meaning of words – closing the gap in understanding between doctors and patients in 21st century consent. (7th August 2020) - Parkinson, Richard; Eardley, Ian; Reynard, John
Abstract : 'When I use a word' Humpty Dumpty said, in a rather scornful tone, 'it means just what I choose it to mean, neither more nor less'. 'The question is' said Alice 'whether you can make words mean so many different things'. Through the Looking‐Glass, Lewis Carroll, 1872.